2005
DOI: 10.4049/jimmunol.175.11.7594
|View full text |Cite
|
Sign up to set email alerts
|

Viral Inhibition of IL-1- and Neutrophil Elastase-Induced Inflammatory Responses in Bronchial Epithelial Cells

Abstract: Previously, we elucidated the intracellular mechanisms by which neutrophil elastase (NE) up-regulates inflammatory gene expression in bronchial epithelial cells. In this study, we examine the effects of both IL-1 and NE on inflammatory gene expression in 16HBE14o− bronchial epithelial cells and investigate approaches to abrogate these inflammatory responses. IL-1 induced IL-8 protein production in time- and dose-dependent fashions, an important observation given that IL-8 is a potent neutrophil chemoattractant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 63 publications
(65 reference statements)
2
18
0
Order By: Relevance
“…Previous studies have identified in part the intracellular signaling pathway regulated by NE (11) and established that NE can induce IL-8 via TLR4 (12). Other studies have demonstrated partial inhibition of NE-induced IL-8 production by using specific inhibitors of TLR signaling in airway epithelial cells (12,13).…”
mentioning
confidence: 99%
“…Previous studies have identified in part the intracellular signaling pathway regulated by NE (11) and established that NE can induce IL-8 via TLR4 (12). Other studies have demonstrated partial inhibition of NE-induced IL-8 production by using specific inhibitors of TLR signaling in airway epithelial cells (12,13).…”
mentioning
confidence: 99%
“…For example, in airway epithelial cells of non-CF and CF origin triacylated lipopeptide, LPS or unmethylated CpG DNA can induce IL-6, IL-8, and TNF-a production via TLRs 2, 4, and 9 (1). Similarly, IL-1b can upregulate production of a plethora of proinflammatory cytokines (2). Therefore, TLRs and their signaling intermediates represent potential therapeutic targets for CF.…”
mentioning
confidence: 99%
“…IL-1RI and TLRs are present on a variety of cell types, including both immune cells and epithelial cells within the lung. In the context of CF, airway epithelial cells have been shown to promote proinflammatory gene transcription following stimulation with their cognate agonists (1,2). For example, in airway epithelial cells of non-CF and CF origin triacylated lipopeptide, LPS or unmethylated CpG DNA can induce IL-6, IL-8, and TNF-a production via TLRs 2, 4, and 9 (1).…”
mentioning
confidence: 99%
“…The vaccinia proteins A46R and A52R inhibit NE and IL-1 induced NF-B activation and IL-8 secretion in airway epithelial cells [114]. A46R also inhibits NF-B activation following stimulation with agonists of TLRs 1, 2, 4, 5, 6, 7 and 9 possibly by virtue of its association with the adaptor protein MyD88.…”
Section: Modulation Of Signalling Downstream Of Trifmentioning
confidence: 99%